Tax Incentives During the Covid-19 Pandemic From The Perspective Of Functional Tax Disseminators - Aruan, Marni; Sudana, I Putu; Widanaputra, Anak Agung Gde Putu; Mimba, Ni Putu Sri Harta (Jurnal Ilmiah Akuntansi dan Bisnis, 2023)
Tax incentives have been provided to taxpayers impacted by the Covid-19 pandemic. The initial implementation of this tax incentive program was suboptimal, one contributing factor being inadequate dissemination of information. However, with the introduction of tax disseminators, the realization of tax incentives has improved. Drawing on role theory and institutional theory, this study seeks to understand the experiences of informants in optimizing tax incentives and their interpretations thereof. A phenomenological method is employed in this research, and data were analyzed using Interpretative Phenomenological Analysis (IPA). The findings reveal that a majority of the informants experienced satisfaction and pride in optimizing tax incentives. These feelings stem from the informants' understanding of their role in implementing tax incentives. The institutional environment shapes the responsibilities and workload of a tax disseminator. Coercive isomorphism arises as all regulations and dissemination guidelines are issued by the Head Office. Keywords: tax incentive, tax disseminator, role theory, institutional theory